Historical ethnobotanical review of medicinal plants used to treat children diseases in Romania (1860s-1970s) - Madalina Petran; Dorin Dragos; Marilena Gilca (BMC, 2020)
Abstract Background Romanian ethnopediatrics has a long history of medicinal plant use. The main objective of the present review was to identify, collect, systematize, and prioritize the available bibliographical data related to medicinal plants traditionally used to treat various pediatric diseases in Romania during the 1860s-1970s. Methods Information was mainly obtained by manual systematic search in various relevant historical works focused on the traditional use of medicinal plants in Romania (1860s-1970s), found in the Archives of Romanian Academy Library and National Romanian Library. Results A total of 153 medicinal plants belonging to 52 families were identified as having ethnopediatric significance. The plant traditional indications, targeted body systems, parts used, and way of administration were provided. We have also proposed one index (expressed as percentage) in order to assess the ethnopediatric applicability area of species: ethnopediatric relative therapeutic versatility (ERTV), which was calculated on the basis of the number of distinct uses mentioned for a species. The species identified to have the highest ERTV scores were Dryopteris filix-mas (100%), Gratiola officinalis (85.71%), Allium sativum (71.42%), Eryngium planum (71.42%), Juglans regia (71.42%), Matricaria chamomilla (71.42%), Plantago major (71.42%). Conclusions The present study exposed for the first time to the international scientific community important ethnopediatric information contained in several local Romanian bibliographical resources that could guide the local and international researchers towards new directions of plant valorization.